A study of cutaneous adverse drug reactions in the dermatology department of a tertiary care teaching hospital in Gujarat - Kalola, Abhishek S.; Shah, Shreya M.; Mistry, Chirag B. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Various drugs are responsible for different cutaneous adverse drug reactions (CADRs). Considering variation in drug responses and the day-to-day increasing burden of ADRs, this study was done with emphasis on the need for effective evaluation and the reporting of the ADR reporting programme. Methods: This was an observational cross-sectional study conducted for the duration of six months in the dermatology department to evaluate various clinical patterns of CADRs. Results: A total of 60 CADRs were reported. Among them, 51.67% were present in males and 48.33% were present in females. The most common CADR was FDE (35%), followed by macula-papular rash (25%). Antimicrobials were most commonly responsible for CADRs, followed by NSAIDs, antiepileptic, anti-gout, and anti-hypertensive medications. Conclusions: For better patient care, drug safety, and rational use of medicines, knowledge of various drugs responsible for CADRs can be useful for health care professionals to reduce mortality and morbidity by monitoring, reporting, and assessment of CADRs whenever detected.